KOMPETENSI SUPERVISI AKADEMIK KEPALA SEKOLAHDALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 3 PEUKAN PIDIE KABUPATEN PIDIE - Nurmalawati .; Cut Zahri Harun; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
One of supervisory functions is to help both school and teachers do their work in order to level up the quality of educational institutions. The objective of this study was to know supervision programs, the implementation supervision, follow up action, and obstacles faced during the academic supervision work to develop teachers’ performance at Elementary School 3 in Peukan Pidie. The method employed in this study was descriptive method with qualitative approach. The data were collected by means of observation, interview, and documentation study. The subjects of this study covered the school principal, and teachers. The research illustrated that: (1) the academic supervision programs to accelerate teachers’ performance had been arranged and documented as outlines. (2) Academic supervision was targeting efforts to develop teachers’ performance. Supervision work covered class supervision, observation class, documentation, interview, questionnaire, and printed reports. (3) Follow up action was done by solving the obstacles faced during supervision. (4) Some of obstacles faced by the principal in doing supervision were problems in the implementation the programs that have been well-planned especially programs to develop teachers’ performance. The principal only have limited time to provide academic supervision to his teachers in terms of correctional and fostering to boost up their performance.Keywords: Academic Supervision, Principal, Teachers’ Performance